2003
DOI: 10.1038/sj.bmt.1704325
|View full text |Cite
|
Sign up to set email alerts
|

Addition of low-dose busulfan to cyclophosphamide in aplastic anemia patients prior to allogeneic bone marrow transplantation to reduce rejection

Abstract: Summary:Busulfan was added at the dose of 4 mg/kg to 200 mg/kg cyclophosphamide in 81 patients (3-53 years, median 24) with aplastic anemia to reduce graft rejection. Graftversus-host disease (GVHD) prophylaxis comprised cyclosporine-methotrexate. The number of prior transfusions was 0-276 (median 26), and 48% had received prior immunosuppressive therapy. Two patients experienced primary graft failure, and 10 secondary rejection at 28-1001 days (median 317 days). The cumulative incidence of rejection was 22%; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 22 publications
2
25
0
3
Order By: Relevance
“…In the present study, we coupled these advantages with the use of fludarabine in the conditioning regimen in order to maximize immunosuppression, reduce toxicity, and avoid graft rejection. We found a cumulative rejection incidence of 26% in heavily transfused patients; in contrast, in a recent study from Brazil, a graft rejection of 43% was observed in 48 polytransfused patients conditioned with cyclophosphamide and low-dose busulfan without ATG and grafted with bone marrow-derived cells [16]. On the other hand, GVHD has a significant impact on survival; in fact, it has been considered in some studies as the major cause of morbidity and mortality [11].…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, we coupled these advantages with the use of fludarabine in the conditioning regimen in order to maximize immunosuppression, reduce toxicity, and avoid graft rejection. We found a cumulative rejection incidence of 26% in heavily transfused patients; in contrast, in a recent study from Brazil, a graft rejection of 43% was observed in 48 polytransfused patients conditioned with cyclophosphamide and low-dose busulfan without ATG and grafted with bone marrow-derived cells [16]. On the other hand, GVHD has a significant impact on survival; in fact, it has been considered in some studies as the major cause of morbidity and mortality [11].…”
Section: Discussionmentioning
confidence: 71%
“…Graft failure has been of concern for many years in SAA patients undergoing an HLA identical BMT. In some centers, busulfan 16 or low-dose TBI 2 has been added to CY to reduce graft failure; in other centers, ATG has been used successfully to reduce graft rejection. 17 In the present series of alternative donor transplants, we have seen an overall graft failure rate of 18%, with a significant age effect: patients aged 15 years or over showed a graft failure rate of 32%, which is significantly higher when compared to younger patients (5%).…”
Section: Discussionmentioning
confidence: 99%
“…The rejection rate was 22% in all 81 patients with acceptable toxicity conditioning with low doses of BU (4 mg/kg)/ CY and the OS was 56% at 8 years in HLA-identical sibling HSCT. 17 To enhance engraftment, BU at the dose of 8 mg/kg was used in our and Xu et al's 4 conditioning regimens. No additional toxicity directly associated with BU was found.…”
Section: Discussionmentioning
confidence: 99%